Element of Loss in Qualifying an Act as an Unlawful Act - Muhammad Hafizhan Armansyah; Adlin Budhiawan (Journal Equity of Law and Governance, 2024)
The aim of this research is to determine the criteria for classifying losses as aspects of criminal acts and the factors judges take into account when classifying losses. This study employs a normative research methodology, which is legal research that views the law as a set of norms. The data sources used in this study are secondary sources, namely journals, Supreme Court Decisions RI Number 2638 K/Pdt/2014, and some laws. Research Results According to R. WirjonoProjodikoro: R. Wirjono Projodikoro interprets the word onrechtmatigedaad as an unlawful act. According to him, the word "deed" in the series of words "unlawful act" can be interpreted positively but also negatively, that is, it also includes things that people can be said to be in violation of the law by just being silent because according to the law, the person should act. It is the duty of judges, particularly constitutional judges, to investigate, uphold, and comprehend the legal principles and sense of justice that permeate society, according to Law Number 48 of 2009, Article 5, paragraph 1. Qualifying events is much more difficult than constatizing events, because constituting events means seeing concrete events, something that can be seen, while qualification in this case is an abstraction rather than the concrete event.